Atypical Imaging Findings in "Central Nervous System Varicella Zoster Virus Vasculopathy Sine Herpete". (April 2022) - Kesav, Praveen; John, Seby; Sajjad, Zafar; Al-Sharif, Khalid; Hussain, Syed I.
Varicella-zoster virus (VZV) infection is notorious for central nervous system involvement, the spectrum of which encompasses vasculopathic manifestations as well. Central nervous system VZV vasculopathy (CVV) most commonly manifests as ischemic strokes or TIA, even though other less common modes of presentation are also well documented in the literature. The pathophysiological mechanism is primarily attributed to active virus infection in the blood vessels secondary to decline in varicella-specific cell-mediated immunity. More than one-third of those with CVV do not have preceding skin lesions of zoster. Hence, a high index of clinical suspicion should be entertained in the appropriate clinical scenario. We hereby describe the case of a 40-year-old lady with systemic lupus erythematosus on long-term oral steroids who presented with acute ischemic stroke involving the right PCA territory, with asymptomatic chronic infarcts in the left MCA. Further evaluation revealed concentric vessel enhancement involving right PCA on high-resolution MR vessel wall imaging with the "Moya-Moya" phenomenon on the left supraclinoid ICA/MCA segment. CSF showed mononuclear pleocytosis with a hemorrhagic component, along with positive VZV DNA PCR. A diagnosis of "CNS VZV Vasculopathy sine herpete" was made and the patient was initiated on appropriate management.